Aloe davyana var. magdae (Asphodelaceae subfam. Alooideae), a distinctive new variety from central-northeastern South Africa - Smith, Gideon F. (Phytotaxa, 2022)
Following the reinstatement of Aloe davyana as an accepted taxon at the rank of species, rather than at that of variety under A. greatheadii, and the subsequent reinstatement of A. davyana var. subolifera, a new variety, A. davyana var. magdae, is here described. Aloe davyana var. magdae, from the southern part of the distribution range of the species, inter alia differs from the pale flesh-pink to dull brick-red-flowered autonymic variety by being more intensely red-flowered, while the other, north-central variety, A. davyana var. subolifera, is most often nearly white-flowered. In addition, the new variety has about twice as many leaves per rosette, in comparison to the autonymic variety and A. davyana var. subolifera.